COVID-19: Understanding the cytokine storm (Research, Society and Development, 2021)
SARS-CoV-2 spread rapidly across China and soon received worldwide attention, prompting the World Health Organization (WHO) to declare, on January 30, 2020, SARS-CoV-2 infection as a public health emergency of international interest. It is a literature review that aims to update and expand the available information about SARS-CoV-2, covering the immune response against it and the consequent formation of the cytokine storm. In some individuals, the immune system exacerbated response causes hyperstimulation of the defense cells, causing hyperinflammation due to the storm of pro-inflammatory cytokines (TNF-α, IL-1-β, IL-6, IL-12 and chemokines). This hyperinflammation characterizes the pathophysiology of severe COVID-19 that causes pathological changes mainly in the lungs, being a predictor of the disease severity due to its strong association with multiple organ failure, which can lead to death. The measurement of serum levels of IL-6 and IL-10 were considered predictors of severe disease and can be used to diagnose patients with a higher risk of worsening the disease. In conclusion, elevations in serum levels of proinflammatory cytokines are usually present in severe COVID-19. However, further studies are needed to establish differences between patients with COVID-19 who develop a protective and balanced inflammatory reaction from those who develop an exaggerated inflammatory reaction, with a consequent pathological cytokine storm.